The role of behavioral activation in the management of depressive symptoms (Research, Society and Development, 2022)
Depression is a complex and multi-causal mental disorder that roundly impacts the individual's life who has its symptoms. It is becoming more possible to observe professionals from different areas of health focusing their studies on the seek to understand this psychological phenomenon, its reach, its ways of acting and working tools. Behavioral activation in depression is a psychotherapy tool, planned as an intervention for the patient's condition, once it is related to the patient's emotions, bringing forth a change in mood and behavior. The present work was developed aiming to describe this tool and it is justified for working with a theme that affects millions of people, discussing more specific ways of working with these symptomatic patterns. The methodology used was the narrative literature review, through the analysis of works that have already been published on the subject. Therefore, it can be concluded that activation acts in the treatment process, reducing avoidance and rumination with techniques: record diary, pleasures that the patient identifies, recording of activities with schedules, handling situational contingencies, verbal rehearsal of proposed tasks and techniques of relaxation, that is, all the steps with the active patient from out to the inside.